The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1965
DOI: 10.1113/jphysiol.1965.sp007724
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of insulin action: the immediate electrochemical effects of insulin on red‐cell systems.

Abstract: While many metabolic effects of insulin on various organs and tissues have been demonstrated, the underlying mechanism of the hormone action has remained obscure. In the present paper evidence will be presented to show that insulin has an immediate electrochemical action on unwashed red cells. In subsequent papers an attempt will be made to relate this action to the hormone's sustained metabolic effects.The distinction between 'immediate electrochemical' and 'metabolic' effects is based on experimental conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
1

Year Published

1965
1965
2003
2003

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…The concentration of extracellular superoxide can be increased by insulin using two different mechanisms: either eNOS secretes superoxide, or insulin activates the NADH/NADPHdependent transmembrane electron transport systems, which produce superoxide extracellularly. [22][23][24] In spite of the many similarities in behavior between endothelial and platelet eNOS functions, we do not have data indicating the existence of caveola-like parts of thrombocyte membranes. 25 …”
Section: Determination Of No • In Biological Systems Is Difficult Beccontrasting
confidence: 53%
“…The concentration of extracellular superoxide can be increased by insulin using two different mechanisms: either eNOS secretes superoxide, or insulin activates the NADH/NADPHdependent transmembrane electron transport systems, which produce superoxide extracellularly. [22][23][24] In spite of the many similarities in behavior between endothelial and platelet eNOS functions, we do not have data indicating the existence of caveola-like parts of thrombocyte membranes. 25 …”
Section: Determination Of No • In Biological Systems Is Difficult Beccontrasting
confidence: 53%
“…Ferricyanide reduction by intact erythrocytes is associated with increased intracellular ATP generation (15), no change in oxygen consumption (15), and proton movement out of the cells (19). The latter likely reflects an attempt of the cell to avoid ferricyanide-induced pH gradients across the cell membrane (20).…”
mentioning
confidence: 99%
“…
The findings reported in the preceding paper (Dormandy & Zairday, 1965) suggested that insulin has an immediate electrochemical effect on unwashed red cells suspended in a variety of simple inorganic saline solutions. The term 'electrochemical' was used to emphasize that experimental conditions and procedures were designed to show up immediate physical rather than sustained metabolic changes.
…”
mentioning
confidence: 92%